Savings Banks of the Soviet Union: A Specific Form of Soviet Credit Institutions (June 1941 – May 1945) - Zotova, Anastasia V. (International Review of Management and Marketing, 2016)
Until now the financial activity of the Soviet state, carried out during the war between Germany and the Soviet Union (USSR) (June 1941 – May 1945) was studied only fragmentarily. Thus, attentions were drawn to the financial activities of the country as a whole, while the history of such an important instrument of financial policy as a savings Bank, has not been studied. Meanwhile, namely the savings Bank were a link between the Soviet government and population of the country. On the basis of numerous Russian archival documents (State archive of the Russian Federation, Russian state archive of the economy, the Central state archive of St. Petersburg) for the first time was analyzed the work of savings banks of collection of funds of Soviet citizens for fighting. At that the dynamics of personnel structure of savings Bank, as well as priority areas of their work were analyzed. Attention is drawn to changes in the activity of savings Bank in military terms. It is emphasized that the savings Bank were not only aimed to maximize the collection of money from the public in the interest of the state financial policy, but also cared about the interest of its clients in the use of this credit institution. Keywords: Great Patriotic war, economy, finance, savings Bank JEL Classifications: R51; O16